Implications of Real-world Adherence on Cost-effectiveness Analysis in Multiple Sclerosis. Issue 4 (April 2013) - Brandes, David W.; Raimundo, Karina; Agashivala, Neetu; Kim, Edward
Abstract Objectives: Adherence to medication is essential for optimal outcomes, especially for chronic diseases such as multiple sclerosis (MS). Studies in MS indicate that lower adherence is associated with an increased risk of relapse, hospitalization or emergency room (ER) visits, and higher medical costs. A previous investigation assessed the cost per relapse avoided for patients with MS receiving first-line disease modifying therapies (DMTs); however, the model assumed 100% adherence. Methods: Because real-world utilization patterns influence the actual effectiveness of medications, this analysis assessed the impact of real-world adherence from a US commercial payer perspective, using updated costs. Results: As was seen in the original study, in this revised model, fingolimod was associated with the lowest cost per relapse avoided ($90, 566), followed by SC IFN β-1b (Extavia: $127, 024), SC IFN β-1b (Betaseron: $137, 492), SC IFN β-1a ($144, 016), glatiramer acetate ($160, 314), and IM IFN β-1a ($312, 629). The model inputs that had the greatest impact on the results were adherence-adjusted relative relapse rate reduction (RRR) of fingolimod, the wholesale acquisition costs of fingolimod, and the average number of relapses in untreated patients with MS. Limitations: The estimates of DMT adherence are from a single claims database study of a large national pharmacy benefit manager that only measured adherence, not actual relapses, and the model does not incorporate manufacturer discounts and rebates, which are not publicly available. Conclusion: These results suggest that economic analyses of MS therapies should incorporate real-world adherence rates where available, rather than relying exclusively on trial-based efficacy estimates when considering the economic value of treatment alternatives, and that highly efficacious therapies with low adherence may yield real-world efficacy that is substantially lower than that observed in closely monitored clinical trials.